The Effect of Problem based learning Model to Improve Students' Mathematical Problem Solving Ability - Hera Cahyawati; Mohamad Salam; Salim (FKIP Universitas Halu Oleo, 2022)
The purpose of this study was to determine the effect of the problem-based learning (PBL) learning model in improving the mathematical problem solving skills of students in class VIII of SMP Negeri 17 Kendari. The population in this study were all VIII grade students of SMP Negeri 17 Kendari consisting of 7 classes, namely VIII1 to VIII7. Determination of class samples as treatment groups was carried out using purposive sampling techniques by considering the average value and variance of the results of students' midterm exam scores in mathematics. Of the two existing class groups carried out by simple randomization so as to obtain two classes that will be used as research samples, namely VIII1 as a control class taught using a team assisted individualization learning model and VIII7 as an experimental class taught using a problem-based learning model. The results of the observation sheet, tests that measure students' mathematical problem solving skills and questionnaires are used as data which will then be analyzed. The results of this study indicate that there is an effect of problem-based learning model in improving mathematical problem solving skills of students in class VIII SMP Negeri 17 Kendari.